2019
DOI: 10.1002/joc.6059
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of tropospheric specific humidity over Iran during 1979–2016

Abstract: In this study, the variation and trend of specific humidity (SH) of the troposphere (1,000–500 hPa) over Iran was analysed using the monthly European Center for Medium Range Weather Forecasting (ECMWF) Re‐Analysis Interim (ERA‐Interim) gridded data from January 1979 to December 2016. By using nonparametric modified Mann–Kendall test, the trend of values for each gridded point was tested in eight different atmospheric levels at 95% confidence level. The Sen's slope estimator test was used to estimate the change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…By the end of the 21st Century, the area-averaged TN90p and TX90p are projected to increase 79% and 74%, respectively. This may be due to an increase of air moisture in the atmosphere in this region by an increase in air temperature, as illustrated by Darand et al (2019). The projected changes in extreme temperature indices over Iran will be helpful for policymakers due to the vast implications for planning and appropriate strategies to adapt to the projected changes.…”
Section: Discussionmentioning
confidence: 99%
“…By the end of the 21st Century, the area-averaged TN90p and TX90p are projected to increase 79% and 74%, respectively. This may be due to an increase of air moisture in the atmosphere in this region by an increase in air temperature, as illustrated by Darand et al (2019). The projected changes in extreme temperature indices over Iran will be helpful for policymakers due to the vast implications for planning and appropriate strategies to adapt to the projected changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to eliminate the influence of significant autocorrelation in the series of data, the researchers employed the modified MK test, in which the series were prewhitened (Jahani et al, 2018). The magnitude of trends were estimated by using a nonparametric Theil-Sen's slope procedure (Sen, 1968;Theil, 1992;Jahani et al, 2018), which is a well-known test (Darand et al, 2019;Delvaux et al, 2019;Yang et al, 2019).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…By contrast, there was an increase, over both land and ocean, in specific humidity and precipitable water in response to the increased temperatures both at the surface and in the troposphere (Gaffen et al 1991;Trenberth et al 2005;Masson-Delmotte et al 2021), with the temperature-moisture relationship being modified by changes in dynamical processes, for example poleward expansion of the Hadley cell (Nguyen et al 2015;Tabari 2020). On the regional scale, Gaffen et al (1991) and Elliott (1996, 2001) reported an increase in specific humidity over most of North America and a small decrease over Europe; Darand et al (2019) found a decrease in specific humidity over most of Iran apart from coastal areas; Hense et al (1988) reported an upward trend of 700-500-hPa precipitable water and RH over the western Pacific; McCarthy et al (2009) found that homogenised radiosonde data show an increase in specific humidity over northern hemisphere extra-tropics; whereas Xie et al (2011) and Zhao et al (2012) found an increase in precipitable water associated with the slight warming in the lower to mid-troposphere over China.…”
Section: Introductionmentioning
confidence: 99%